2015
DOI: 10.1007/s00436-015-4728-0
|View full text |Cite
|
Sign up to set email alerts
|

Where are the sensory organs of Nybelinia surmenicola (Trypanorhyncha)? A comparative analysis with Parachristianella sp. and other trypanorhynchean cestodes

Abstract: The sensory organs in tegument of two trypanorhynchean species--Nybelinia surmenicola (plerocercoid) and adult Parachristianella sp. (Cestoda, Trypanorhyncha)--were studied with the aim of ultrastructural description and a comparative analysis. The Nybelinia surmenicola plerocercoid lacks papillae with sensory cilia on the bothria adhesive surface. We found an unciliated sensory organ within the median bothria fold. This unciliated free nerve ending contains the central electron-dense disc, three dense support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…In contrast to the diversity of shapes of the spinitriches (Chervy, ), the filitriches slightly differ internally in the relative length of the cap and the base, as it has been reported in some trypanorhynchs (Biserova et al, ; Palm et al, ). In O. schmittii, the spinitriches have caps that are longer than the base (cap/base length ratio up to 1:0.43), whereas most filitriches have short caps and longer bases (cap/base length ratio over 1:1.06), except on the apical suckers (ratio cap/base length ratio 1:0.37), and the distal bothridial surface (ratio cap/base length ratio 1:0.67–1.43).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In contrast to the diversity of shapes of the spinitriches (Chervy, ), the filitriches slightly differ internally in the relative length of the cap and the base, as it has been reported in some trypanorhynchs (Biserova et al, ; Palm et al, ). In O. schmittii, the spinitriches have caps that are longer than the base (cap/base length ratio up to 1:0.43), whereas most filitriches have short caps and longer bases (cap/base length ratio over 1:1.06), except on the apical suckers (ratio cap/base length ratio 1:0.37), and the distal bothridial surface (ratio cap/base length ratio 1:0.67–1.43).…”
Section: Discussionmentioning
confidence: 85%
“…Sensory receptors similar to the Type B receptor of O. schimittii (i.e., having a cilium, and two electro‐dense supporting rings) were observed in Gyrocotylidea (Allison, ), Diphyllobothriidea (Mustafina & Biserova, ), Cyclophyllidea (Webb & Davey, ), Trypanorhyncha (Biserova et al, ; Casado et al, ; Palm et al, ), and Onchoproteocephalidea (Brunanska et al, ). Some authors have suggested that these receptors might act as mechanoreceptors based on their position in attachment organs such as the rosette of gyrocotylideans, or the bothria of trypanorhynchs (Allison, ; Palm et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations